The elusive concept of sexual motivation: can it be anchored in the nervous system? - Ventura-Aquino, Elisa; Ågmo, Anders (Frontiers in Neuroscience, 2023)
Sexual motivation is an abstract concept referring to the mechanisms determining the responsivity to sexually relevant stimuli. This responsivity determines the likelihood of producing a sexual response and the intensity of that response. Both responsivity to stimuli and the likelihood of making a response as well as the intensity of response are characteristics of an individual. Therefore, we need to assume that the concept of sexual motivation materializes in physiological mechanisms within the individual. The aim of the present communication is to analyze the requisites for the endeavor to materialize sexual motivation. The first requisite is to provide an operational definition, making the concept quantifiable. We show that parameters of copulatory behavior are inappropriate. We argue that the intensity of sexual approach behaviors provides the best estimate of sexual motivation in non-human animals, whereas the magnitude of genital responses is an exquisite indicator of human sexual motivation. Having assured how to quantify sexual motivation, we can then proceed to the search for physiological or neurobiological underpinnings. In fact, sexual motivation only manifests itself in animals exposed to appropriate amounts of gonadal hormones. In female rats, the estrogen receptor α in the ventrolateral part of the ventromedial nucleus of the hypothalamus is necessary for the expression of sexual approach behaviors. In male rats, androgen receptors within the medial preoptic area are crucial. Thus, in rats sexual motivation can be localized to specific brain structures, and even to specific cells within these structures. In humans, it is not even known if sexual motivation is materialized in the brain or in peripheral structures. Substantial efforts have been made to determine the relationship between the activity of neurotransmitters and the intensity of sexual motivation, particularly in rodents. The results of this effort have been meager. Likewise, efforts of finding drugs to stimulate sexual motivation, particularly in women complaining of low sexual desire, have produced dismal results. In sum, it appears that the abstract concept of sexual motivation can be reliably quantified, and the neurobiological bases can be described in non-human animals. In humans, objective quantification is feasible, but the neurobiological substrate remains enigmatic.